Pneumocystis jirovecii pneumonia in HIV-negative patients: A prospective study with focus on immunosuppressive drugs and markers of immune impairment. (March 2014) - Roblot, France; Le Moal, Gwenael; Kauffmann-Lacroix, Catherine; Bastides, Frederic; Boutoille, David; Verdon, Renaud; Godet, Cendrine; Tattevin, Pierre; ,
Abstract Pneumocystis jirovecii pneumonia (PCP) is emerging in HIV-negative patients, for whom the prognosis is significantly worse than in HIV-infected patients and risk factors are poorly characterized. We performed an observational, multi-centre, prospective study of 56 consecutive cases of documented PCP in HIV-negative patients, and found that: (1) the main underlying conditions were haematological malignancies (43%), solid tumours (25%), inflammatory diseases (20%), and solid organ transplantation (7%); (2) most patients (80%) had received prolonged corticosteroids, with a mean daily dose of 47.3 ± 32.8 mg equivalent prednisone when PCP was diagnosed, and a mean cumulative dose of 5807 ± 5048 mg over the last 12 months; and (3) the median CD4 cell count was 0.12 × 109/l (range 0.0–1.42), with a median CD4/CD8 ratio of 1.32 (0.0–6.4). These findings may be used to better target PCP prophylaxis according to the level of risk and contribute to decrease the burden of PCP in HIV-negative patients.